Emergy distribution in oxidation pond and constructed wetland treating a domestic wastewater - Thaneeya Perbangkhem (2018)
Two identical pilot-scale reactors - one as an oxidation pond (OP) and the other as a freewater- surface-flow constructed wetland (CW) planted with Cyperus papyrus - were fed with a lowstrength domestic wastewater at the organic loading rate of 16 kg BOD/ha-d. The purpose of this study was to investigate how the solar energy dissipated into the biomass productivities during the wastewater treatment course, using emergy analysis. In the experiments, both treatment systems were operated with daily draw-and-fill mode for two months. After that, the biomass productivities were measured from the weight increases and effluent samplings were performed to bring about laboratory analysis of water-quality parameters. Based on the emergy analyses, the CW unit was found to use lower emergy for pollutant removal, corresponding to the lesser ecological waste removal potential (EWRP) than that of OP unit. As the algal cells were dominant in the OP, they contributed to 80 percent of the total emergy input, resulting in a highly turbid effluent. The emergy transfer was found to be most effective in the CW unit with the efficiencies of 6 and 67 percent for plant and fish productions, respectively. Thus, the comparative emergy assessment performed in this study indicated a higher potential of CW over OP to be used for, not only pollution control, but also biomass productions of fish and wetland plant for further human's utilization.